Anthropogenic noise alters parental behavior and nestling developmental patterns, but not fledging condition. (23rd April 2021) - Pandit, Meelyn Mayank; Eapen, James; Pineda-Sabillon, Gabriela; Caulfield, Margaret E; Moreno, Alexander; Wilhelm, Jay; Ruyle, Jessica E; Bridge, Eli S; Proppe, Darren S
Abstract: Anthropogenic noise is a ubiquitous feature of the American landscape, and is a known stressor for many bird species, leading to negative effects in behavior, physiology, reproduction, and ultimately fitness. While a number of studies have examined how anthropogenic noise affects avian fitness, there are few that simultaneously examine how anthropogenic noise impacts the relationship between parental care behavior and nestling fitness. We conducted Brownian noise playbacks for 6 h a day during the nesting cycle on Eastern Bluebird ( Sialia sialis ) nest boxes to investigate if experimentally elevated noise affected parental care behavior, nestling body conditions, and nestling stress indices. We documented nest attendance by adult females using radio frequency identification (RFID), and we assessed nestling stress by measuring baseline corticosterone levels and telomere lengths. Based on the RFID data collected during individual brood cycles, adult bluebirds exposed to noise had significantly higher feeding rates earlier in the brood cycle than adults in the control group, but reduced feeding rates later in the cycle. Nestlings exposed to noise had higher body conditions than the control nestlings at 11 days of age, but conditions equalized between treatments by day 14. We found no differences in nestling baseline corticosterone levels or nestling telomere lengths between the two treatment groups. Our results revealed that noise altered adult behavior, which corresponded with altered nestling body condition. However, the absence of indicators of longer-term effects of noise on offspring suggests adult behavior may have been a short-term response. Abstract : Human-induced noise can alter avian behavior, which can affect offspring condition and fitness. We examined how noise would affect parental care in eastern bluebirds by experimentally elevating noise levels at the nest box. Adult bluebirds exposed to noise initially had higher visitation rates to the nest box, which led to higher nestling body conditions, than adults in the control treatment. However, noise-exposed adult visitation rates decreased as the nestling grew older.